Association of plasma angiogenin with risk of major cardiovascular events in type 2 diabetes - Gurung, Resham L. (2024)
Background: Angiogenin, an enzyme belonging to the ribonucleases A superfamily, plays an important role in vascular biology. Here, we sought to study the association of plasma angiogenin and major adverse cardiovascular events (MACEs) in patients with type 2 diabetes (T2D). Methods: This prospective study included 1083 T2D individuals recruited from a secondary hospital and a primary care facility. The primary outcome was a composite of four-point MACE (nonfatal myocardial infarction, stroke, unstable angina pectoris leading to hospitalization and cardiovascular death). Circulating angiogenin was measured by a proximity extension assay. Cox regression models were used to evaluate the association of baseline plasma angiogenin with the risk of MACE. Results: During a median follow-up of 9.3 years, 109 (10%) MACE were identified. Plasma angiogenin was significantly higher in participants with MACE than in those without MACE (P < 0.001). Doubling of plasma angiogenin concentration was associated with a 3.10-fold (95% CI 1.84–5.22) increased risk for MACE. The association was only moderately attenuated after adjustment for demographic and cardiometabolic risk factors (adjusted HR 2.38, 95% CI 1.34–4.23) and remained statistically significant after additional adjustment for estimated glomerular filtration rate (eGFR) and urinary albumin to creatinine ratio (uACR) (adjusted HR 1.90, 95% CI 1.02–3.53). A consistent outcome was obtained when plasma angiogenin was analysed as a categorical variable in tertiles. Conclusions: Plasma angiogenin was associated with the risk of future cardiovascular events in patients with T2D and may be a promising novel biomarker for identifying high-risk T2D patients for early management.